IMPLEMENTASI KEGIATAN EKSTRAKURIKULER KARYA TULIS ILMIAH UNTUK MENGEMBANGKAN BAKAT SISWA IPS DI MAN MODEL BOJONEGORO - Sa’diyah, Halimatus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aims to: (1) Describe the program of extracurricular activities of scientific papers to develop the talents of IPS students in MA del Bojonegoro, (2) Describe Implementation of extracurricular activities of scientific papers to develop the talents of IPS students in MAN Model Bojonegoro, (3) Knowing the obstacles and solutions in extracurricular activities of scientific papers to develop the talents of IPS students in MAN Model Bojonegoro. The type of research is field research (field research) and using a descriptive qualitative approach. Data collection techniques used are observation, interview, documentation and triangulation. Data is analyzed using the following scheme: data collection, reduction, data presentation and conclusion. The results of the research show as follows: (1) The program of extracurricular activity of scientific writing is a prominent activity, this activity is presented so that students can develop talents in the field of IPS in terms of writing and research, extracurricular activities of scientific papers have been running well with the enthusiasm of students in following the activities (2) Implementation of extracurricular activities of scientific papers the field of IPS include: (a) The material is choosing learning materials according to the conditions and circumstances surrounding the students (b) The method used Â includes lecture, discussion, question and answer and assignment. (c) Media, include media of view and view of hearings such as, laptops, LCD and loudspeakers; (d) Evaluation include: the techniques of evaluation of assignments, practices, and comparing the quality of scientific papers students from year to year. (3) Obstacles in extracurricular activities of scientific papers to develop the talents of IPS students in MAN Model Bojonegoro namely the constraints of facilities and infrastructure and time constraints. The solution of the school is by the addition of adequate infrastructure, especially internet access and additional reading and addition of time allocation.Keywords: implementation, extracurricular, activities of scientific writing, IPS.